Lack of evidence for the association of ornithine decarboxylase (+316 G>A), spermidine/spermine acetyl transferase (‑1415 T>C) gene polymorphisms with calcium oxalate stone disease - Çoker Gürkan, Ajda; Arısan, Serdar; Ünsal, Zeynep Narçin; ARISAN, ELİF DAMLA (My University, 2013)
Urolithiasis is a complex and multifactorial disorder characterized by the presence of stones in the urinary tract. Urea cycle is an important process involved in disease progression. L‑ornithine is a key amino acid in the urea cycle and is converted to putrescine by ornithine decarboxylase (ODC). Putrescine, spermidine and spermine are natural polyamines that are catabolized by a specific enzyme, spermidine/spermine acetyltransferase (SSAT). The single‑nucleotide polymorphisms (SNPs) in the intron region of ODC (+316 G>A) and promoter region of SSAT (‑1415 T>C) genes have been found to be associated with the polyamines expression levels. The aim of this study was to examine whether the ODC (+316 G>A) intron 1 region gene polymorphism and SAT‑1 promoter region (‑1415 T>C) gene polymorphisms are potential genetic markers for susceptibility to urolithiasis. A control group of 104 healthy subjects and a group of 65 patients with recurrent idiopathic calcium oxalate stone disease were enrolled into this study. Polymerase chain reaction (PCR)‑based restriction analysis was performed for the ODC intron 1 (+316 G>A) region and SAT‑1 (‑1415 T>C) promoter gene polymorphisms by PstI and MspI restriction enzyme digestion, respectively. The genotype distribution of polymorphisms studied in the ODC intron 1 region (+316 G>A) and SAT‑1 ‑1415 T>C promoter region did not reveal a significant difference between urolithiasis and the control groups (P=0.713 and 0.853), respectively. Furthermore, no significant difference was observed between the control and patient groups for ODC +316 G>A and SAT‑1 ‑1415 T>C allele frequencies (P=0.877 and 0.644), respectively. In conclusion, results of the present study suggest that ODC + 316 G>A and SAT‑1 ‑1415 T>C gene polymorphisms might not be a risk factor for urolithiasis.